2000
DOI: 10.1016/s0969-6989(00)00019-9
|View full text |Cite
|
Sign up to set email alerts
|

Consumer and retailer perceptions of hypermarkets and traditional retail stores in Portugal

Abstract: Since its appearance in the mid 1980s, the hypermarket is a symbol of the modernisation of Portugal. It has dramatically changed not only the retailing structure in this country but also Portuguese buying behaviour. To better understand these changes, personal interviews were conducted with 500 Braga consumers. In addition, a mailed survey was administered in the same market to 204 traditional retailers. The results show that, for consumers, the hypermarket is the preferred type of retail store for frequently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 13 publications
4
25
1
2
Order By: Relevance
“…Initially, it was though that a possible explanation for these results might lie in the countries' relatively low levels of purchasing power. Previous studies have shown Portuguese consumers to be far more concerned with price as a purchasing criterion than their counterparts from richer European countries, whose interests lie far more in aspects such as quality, for example (FARHANGMEHR et al, 2000). A lower purchasing power and greater preoccupation with price may mean that issues such as corporate social responsibility or firm ethicality simply become secondary to consumers, as reflected in the results obtained.…”
Section: H1mentioning
confidence: 67%
“…Initially, it was though that a possible explanation for these results might lie in the countries' relatively low levels of purchasing power. Previous studies have shown Portuguese consumers to be far more concerned with price as a purchasing criterion than their counterparts from richer European countries, whose interests lie far more in aspects such as quality, for example (FARHANGMEHR et al, 2000). A lower purchasing power and greater preoccupation with price may mean that issues such as corporate social responsibility or firm ethicality simply become secondary to consumers, as reflected in the results obtained.…”
Section: H1mentioning
confidence: 67%
“…Hypermarkets with ever larger areas dedicated to a greater variety of products that can feed shoppers' hedonic shopping desires (Weitz & Whitfield., 2010), while maintaining other areas stocked with grocery products in tight grid formats that are primarily orientated toward satisfying utilitarian needs (Sloot et al, 2005). Research undertaken by Farhangmehr et al (2000) found that hypermarkets are preferred choice for customers who frequently purchased packaged goods, due to its low prices and convenient onestop shopping.…”
Section: Shopping Motivation On Purchase Intentionmentioning
confidence: 99%
“…At the same time, modern retailers might have a negative impact on local retailers (Farhangmehr, Marques, & Silva, 2000;Jones & Doucet, 2000;McGee, 1996). The opening of large retailers in a given area usually leads to market exit by small retailers unable to compete against large retailers that have greater buying power and more resources than small stores.…”
Section: Economic Retailer Brand Image Attributesmentioning
confidence: 99%